Long-Term Response to PD-1 and CTLA-4 Blockade in an SCLC Patient with Negative PD-L1 Expression on Biopsy: A Case Report - Marco Cefalì; Francesco Martucci; Patrizia Frösch (healthbook TIMES. Oncology Hematology, 2023)
# Introduction